1990
DOI: 10.1002/jlb.47.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cell Activity and Macrophage-Dependent Inhibition of Growth or Killing of Mycobacterium avium Complex in a Mouse Model

Abstract: Natural killer (NK) cells from spleens of normal and Mycobacterium avium complex (MAC)-infected C57 black mice (C57 BL/6 bg/+) were examined for their capacity to activate splenic and peritoneal macrophages from beige mice to inhibit or kill intracellular MAC. Peritoneal and splenic macrophages from beige mice were exposed in vitro to NK cells obtained from MAC-infected and uninfected black mice. NK cells from uninfected black mice were also treated in vitro with recombinant interleukin-2 (IL-2) for 48 h befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…The first report on the role of NK cells during bacterial infection was related to their capacity to lyse either Shigella flexneri-infected HeLa cells (18), Legionella pneumophila-infected monocytes (19) or Mycobacterium avium-infected monocytes (20). The latter study also reported that NK cells could help macrophages to inhibit growth or kill intracellular bacilli (21). Similar findings were reported for Mycobacterium lepraemurium (22).…”
Section: Antibacterial Innate Immunitymentioning
confidence: 61%
See 1 more Smart Citation
“…The first report on the role of NK cells during bacterial infection was related to their capacity to lyse either Shigella flexneri-infected HeLa cells (18), Legionella pneumophila-infected monocytes (19) or Mycobacterium avium-infected monocytes (20). The latter study also reported that NK cells could help macrophages to inhibit growth or kill intracellular bacilli (21). Similar findings were reported for Mycobacterium lepraemurium (22).…”
Section: Antibacterial Innate Immunitymentioning
confidence: 61%
“…For example, the protective role of NK cells was demonstrated in infections induced by M. avium, M. lepraemurium or M. tuberculosis (20)(21)(22)(23)194,195). The protective role of NK cells was also demonstrated in models of infection with different strains of Salmonella (196)(197)(198).…”
Section: Benefits Versus Disadvantages Of Nk Cell Activation During Bmentioning
confidence: 99%
“…Phenotypically, these deficiencies make them more susceptible to pyogenic bacterial infections. Beige mice have been utilized extensively to study M. avium infections and experimental chemotherapy in AIDS patients (21,22,122). When inoculated intravenously with ca.…”
Section: Animal Modelsmentioning
confidence: 99%
“…In mice, resistance to early growth of M. bovis, M. lepraemurium, M. intracellulare, and M. avium may be controlled by a single dominant autosomal gene, Bcg (424). Furthermore, phagocytosis-or ligand-induced respiratory burst activity is significantly greater in macrophages from resistant animals than in macrophages from susceptible mice (372), and the transfer of immune cells (T or NK cells) from resistant to susceptible mice is associated with an increased ability of the latter animals to control M. avium infection (31). However, these observations contradict the observation that peritoneal macrophages from MAC-resistant and MAC-susceptible mice have equal capacities to ingest and inhibit or kill MAC in vitro (31).…”
Section: Immune Response Cellular Immunitymentioning
confidence: 99%